Potential Settlement Due to Seismic Effects in the Residential Area of Ilgin (Konya, Turkey) (2016)
Ilgin lies on newly formed, loose, granular deposits, and there is a substantial risk for surface liquefaction and foundation settlements due to the seismic effects resulting from groundwater close to the surface. This study evaluates potential settlement due to seismic effects in the residential areas of Ilgin using the Standard Penetration Test (SPT) performed on 45 geotechnical bores. In Turkey, where earthquakes occur frequently, the selection of residential areas is of great importance. In this research, the number of settlements was calculated considering an earthquake having a Local Magnitude of 6 (i.e., ML ≥ 6.0 and a ≥ 0.4 g) under a 0.4 g seismic force, and a potential settlement map of the residential area was prepared. The amount of settlement exceeds 20 cm at locations near Ilgin Lake and in the northern section of Ilgin residential areas; downtown, the settlement ranges from 10-20 cm. The settlements presented here exceed the allowable threshold limits for structures constructed using adobe and brick in this district. Thus, improvements to minimize earthquake-induced damages are required for structures in Ilgin. Moreover, the selection of new residential areas, along with the proper design of the structures before construction, should be examined further to avoid ground liquefaction and structure damage due to settlement.  ResumenLa localidad de Ilgin está ubicada sobre depósitos recién formados, granulares y no compactos, por lo que existe un riesgo sustancial de licuefacción de la superficie y la creación de asentamientos o deslizamientos debido a los efectos sísmicos resultantes del agua subterránea poco profunda. Este artículo evalúa el potencial de asentamiento debido a los efectos sísmicos en las áreas residenciales de Ilgin a través del Ensayo de Penetración Estándar (SPT, en inglés) realizado en 45 perforaciones geotécnicas. En Turquía, donde los terremotos ocurren frecuentemente, la selección de áreas residenciales es de gran importancia. En esta investigación, se calculó el número de asentamientos ante un terremoto con Magnitud Local (ML) de 6 y con una fuerza sísmica de 0.4 g para preparar un mapa de asentamientos en el área residencial. La cantidad de asentamientos supera los 20 centímetros en lugares cercanos al lago Ilgin y en la sección norte del área residencial; en el centro, los rangos de asentamiento van de 10 a 20 cm. Los asentamientos presentados exceden los límites de lo permitido para estructuras construidas en adobe y ladrillo en este distrito. Por esto, se requieren mejoras para minimizar los daños inducidos por terremotos en las estructuras de Ilgin. Además, la selección de nuevas áreas residenciales, junto con el diseño apropiado de las estructuras antes de la construcción, debe ser revisado atentamente para evitar la licuefacción del suelo y el daño de las estructuras debido al asentamiento.